2015
DOI: 10.1177/0021998315592007
|View full text |Cite
|
Sign up to set email alerts
|

Wear properties of Al–Al2O3/TiB2 surface hybrid composite layer prepared by friction stir process

Abstract: In this study, surface hybrid composite was fabricated on Al6061 base sheets using friction stir processing (FSP). Samples were subjected to various numbers of FSP passes from one to four with Al2O3/TiB2 powder. Influence of number of FSP passes was studied on distribution of Al2O3/TiB2 particles in aluminium matrix, microstructure, hardness, and wear properties of specimens. The results showed that increase in the number of passes causes a more uniform dispersion of composite particles and thus, decreases par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…AZ31 alloy is known for its superior mechanical properties widely applied in aircraft industries which has aluminium and zinc as major alloying elements of around 3 and 1% respectively. The choice of silica-rich HNT as the primary reinforcement was motivated by its high strength, green nature, corrosion resistance, wear resistance, and non-toxic properties [21,22]. HNT with a structural formula of (H 4 AL 2 O 9 Si 2 .2H 2 O) with an average particle size of 40 nm is utilized.…”
Section: Methodsmentioning
confidence: 99%
“…AZ31 alloy is known for its superior mechanical properties widely applied in aircraft industries which has aluminium and zinc as major alloying elements of around 3 and 1% respectively. The choice of silica-rich HNT as the primary reinforcement was motivated by its high strength, green nature, corrosion resistance, wear resistance, and non-toxic properties [21,22]. HNT with a structural formula of (H 4 AL 2 O 9 Si 2 .2H 2 O) with an average particle size of 40 nm is utilized.…”
Section: Methodsmentioning
confidence: 99%
“…AA5083 MMCs display several interesting mechanical and physical properties such as considerable strength, low density, significant corrosion resistance, considerable fatigue strength, and improved friction and wear behaviour. Numerous studies have reported the incorporation of several reinforcements to aluminium alloys to improve the tribological characteristics and surface properties such as B 4 C [ 1 , 2 , 3 ], Al 2 O 3 [ 4 , 5 ], SiC [ 6 , 7 , 8 ], TiC [ 9 ], TiO 2 [ 10 ], and ZrO 2 [ 11 ]. Many techniques have been used to fabricate Al-based metal matrix composites such as powder metallurgy, casting technology, and friction stir processing (FSP) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the properties of high hardness and high wear resistance, ceramic particles such as SiC and TiB2 as a reinforcing phase have been widely used in wear-resistant parts of aluminum-based composites [1]. However, the physical properties of the aluminum matrix and the ceramic particles are quite different, such as the coefficient of thermal expansion, which leads to greater stress when the two materials are combined, and the reinforcement phase is easily peeled off during service, affecting the wear resistance.…”
Section: Introductionmentioning
confidence: 99%